1998
DOI: 10.1002/(sici)1099-0518(19980915)36:12<2119::aid-pola18>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of styrene with nickel complex/methylaluminoxane catalytic systems

Abstract: Polymerization of styrene using catalytic systems based on nickel derivatives and methylaluminoxane (MAO) was studied. Among tested catalysts, nickel bis(acetylacetonate) and nickel dichloride show the maximum activity. Bis(phosphine)nickel dichlorides exhibit lower activity, depending on the nature of the phosphine ligand. Polymer yields decrease by lowering the catalyst concentration, by increasing the reaction temperature, or by carrying out the polymerization in a polar donor solvent. Weight average molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 4 publications
4
70
0
Order By: Relevance
“…Based on what it is known about the behavior of Ni(acac) 2 /MAO, 4 this last segment is likely to be isotactic (%mB70) and much shorter than the syndiotactic block: the lengths, estimated from the here-reported experimental meso diads content and typical meso diads content values found for iPS and sPS produced by Cp* catalysts, are about 5% of the syndiotactic block.…”
Section: Isotactic-capped Syndiotactic Polystyrenementioning
confidence: 72%
See 1 more Smart Citation
“…Based on what it is known about the behavior of Ni(acac) 2 /MAO, 4 this last segment is likely to be isotactic (%mB70) and much shorter than the syndiotactic block: the lengths, estimated from the here-reported experimental meso diads content and typical meso diads content values found for iPS and sPS produced by Cp* catalysts, are about 5% of the syndiotactic block.…”
Section: Isotactic-capped Syndiotactic Polystyrenementioning
confidence: 72%
“…When they are combined, in principle, if the catalytic centers were independent the final products would be complex mixtures of polymers having different tacticities: sPS (afforded by titanium sites); iPS (afforded by nickel sites); and aPS (afforded by MAO and other non-stereospecific sites). As hot methyl ethyl ketone (MEK) dissolves aPS and iPS (up to %m¼90), 4 as well as the low-molecular-weight fraction of sPS, 14 extraction with MEK was applied to isolate the syndiotactic fraction for a better elucidation of the products structure. The results are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Half-sandwich complexes of cyclopentadiene and substituted cyclopentadienes with titanium as the metal especially showed a high polymerization activity as well as a high proportion of syndiotactic polymer in combination with MAOs or boron organic compounds. [2][3][4] Although the cyclopentadienyl ring of the titanium compound has experienced a wide structure variation in the search for catalysts with a higher polymerization activity, much less attention has been paid to the variation of the other ligands of the metal cyclopentadienyl compound.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Syndiotactic polystyrene (sPS) is a new semicrystalline polymer with a melting temperature of about 270 C. Its high heat-resistance and modulus of elasticity, excellent resistance to chemicals and relatively fast crystallization rate make sPS a potential thermoplastic for a large number of applications in automotive and electronic industries. 5 It has gained increasing academic and industrial interests since its first successful synthesis using a metallocene catalyst as reported by Ishihara. 6 Despite these desirable properties, a disadvantage of sPS is its inherent brittleness.…”
mentioning
confidence: 99%